Analisis Kandungan Gizi Dan Daya Terima Panelis Terhadap Kudapan Gyobas Berbasis Ikan Bandeng Sebagai Upaya Pencegahan Anemia Dan Stunting Pada Remaja - Sunarto, Sunarto; Irma, Rita; Chaerunnimah, Chaerunnimah (Direktorat Politeknik Kesehatan Makassar, 2024)
The panelist respondents were 30 people. The acceptability of the product is assessed using a hedonic test scale form which consists of strongly dislike, dislike, somewhat like (neutral), like and very like. The nutritional content of the product is assessed using the Indonesian food composition table (TKPI), 2020. Analysis of nutritional composition using TKPI shows that 100 g of Gyobas snack contains 261.5 kcal energy, 11.5 g protein, 11.5 g fat, 8 g carbohydrates, 3.5 g fiber, 0.5 mg Vitamin B1, vitamin C 6.0 mg, total carotene 398 g, ash 0.5 g, calcium 20 mg, phosphorus 74 mg, iron 1.0 mg, sodium 285 mg, potassium 128 mg, copper 11 mg, zinc 0.5 mg . The organoleptic test results show that Gyobas snacks can be accepted with a percentage of acceptance on a scale of like to really like, in the color aspect the total acceptance level is 87%, the aroma aspect is 93%, the texture aspect is 93% and the taste is 100%. Based on the average hedonic value for the aspects of color, aroma, texture and taste, each of which is 4.2; 4,4, ; 4.3 and 4.6. The nutritional value of Gyobas snacks is quite complete, covering macro and micro nutrients so that it can be an alternative snack based on local food as an effort to prevent nutritional problems (Anemia or Stunting) in teenagers. Overall, Gyobas were liked and accepted by the panelists, but the taste aspect had the highest level of acceptance. Keywords: Acceptability, Milkfish, Gyoza, Gyobas, Anemic and Stunting.